Knowledge domain and hotspots analysis concerning applications of two-photon polymerization in biomedical field: A bibliometric and visualized study - Fu, Hongxun; Jing, Xian; Lin, Jieqiong; Wang, Liye; Jiang, Hancheng; Yu, Baojun; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2022)
Two-photon polymerization (TPP) utilizes an optical nonlinear absorption process to initiate the polymerization of photopolymerizable materials. To date, it is the only technique capable of fabricating complex 3D microstructures with finely adjusted geometry on the cell and sub-cell scales. TPP shows a very promise in biomedical applications related to high-resolution features, including drug delivery, tissue engineering, microfluidic devices and so forth. Therefore, it is of high significance to grasp the global scientific achievements in this field. A bibliometric and visualized study of publications concerning the application of TPP in the biomedical field was performed, and the knowledge domain, research hotspots, frontiers, and research directions in this topic were identified according to the research results.